UNIVERSITY MANAGEMENT IN THE LIGHT OF SENSEMAKING AND PRACTICES: AN INTEGRATIVE LITERATURE REVIEW - Silva Cougo, Juliano; Ribeiro Diniz, Iasmin; Thaiane Tercino de Araújo, Elisabeth; Flávio Tonelli, Dany (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2025)
Objective: This article aims to investigate, through the theoretical lenses of sensemaking and practice theories, how university reorganizations have been addressed in specialized literature. Design/Method/Approach: This is an integrative bibliographical research that identified 14 studies aligned with the established criteria, emphasizing sensemaking processes and practical developments resulting from organizational changes in the university context. Originality/Relevance: The study stands out by integrating two complementary theoretical approaches – sensemaking and practice theories – to examine the transformations experienced by higher education institutions in recent decades, particularly under the influence of autonomy policies and market logic. Key Results/Findings: The main findings include: (i) the ways institutional autonomy has been operationalized through emancipated management systems; (ii) the implementation of curricular guidelines focused on student performance in the labor market; and (iii) concerns of professors and department heads who tend to question their roles as strategic leaders within universities. Theoretical and Practical Contributions: The study contributes to the academic community by highlighting the adversities, challenges, and meaning-making processes developed by university actors in response to organizational transformations, providing insights for future research.